Interdisciplinary Concepts in Cardiovascular Health Volume III: Cardiovascular Events - Wakabayashi, Ichiro; Groschner, Klaus (Springer International Publishing : Imprint: Springer, 2014)
This book provides an introduction to the principles of both cardiovascular epidemiology and molecular pathophysiology; as a unique aspect, it also outlines and discusses the molecular concepts underlying epidemiological observations. This third volume is focused on the most common "cardiovascular events" to provide an overview on pathogenesis and clinical aspects. The book promotes the use of interdisciplinary approaches in the field of preventive medicine based on recent advances in molecular and cellular pathophysiology. The book offers a valuable resource for researchers in basic biomedical fields and clinical scientists alike, as well as guidelines for novel avenues of research in both basic pathophysiology and cardiovascular therapy and prevention.